A Chlorine-Bearing Asymmetric Center as a Stereocontrol Element in a Short Formal Synthesis of Steviol - Michalak, Sharon E.; Vanderwal, Christopher D. (Synthesis, 2025)
Steviol is one of the myriad polycyclic terpenoids bearing oxygenation on the axially disposed C19 carbon. The presence of this C19 alcohol renders the C4 quaternary carbon stereogenic, issuing a challenge for stereoselective synthesis. Here we show that a suitably disposed chlorine atom at C2, coupled with the correct diastereomer of terminal epoxide that initiates cationic bicyclization, leads to the desired stereochemical outcome. Subsequently, the anisole terminating group undergoes Birch reduction that simultaneously reduces the C–Cl bond, removing the transient “auxiliary” and completing a short, highly stereoselective formal synthesis of steviol. This work provides another example of the power of removable C–X bonds for stereocontrolled synthesis.
Keywords: Cyclizations; Chlorine; Epoxide; Terpenoids; Total synthesis; Stereoselectivity